2014
DOI: 10.1016/j.atherosclerosis.2013.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and liraglutide ameliorate high glucose-induced oxidative stress via inhibition of PKC-NAD(P)H oxidase pathway in human aortic endothelial cells

Abstract: Metformin and liraglutide ameliorate high glucose-induced oxidative stress by inhibiting PKC-NAD(P)H oxidase pathway. A combination of these two drugs provides augmented protective effects, suggesting the clinical usefulness in prevention of diabetic vascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 42 publications
5
99
1
Order By: Relevance
“…8) Liraglutide, a glucagon-like peptide-1 analogue, has been found to inhibit oxidative stress and inflammatory response in the endothelial cells, heart and brain. 19,20,22,23) Results obtained from the present study contribute to further understanding of the mechanisms whereby liraglutide exerts a protective effect against high fat and high cholesterol diet induced hepatic steatosis, insulin resistance and liver dysfunction. Administration of liraglutide effectively alleviated hepatic oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…8) Liraglutide, a glucagon-like peptide-1 analogue, has been found to inhibit oxidative stress and inflammatory response in the endothelial cells, heart and brain. 19,20,22,23) Results obtained from the present study contribute to further understanding of the mechanisms whereby liraglutide exerts a protective effect against high fat and high cholesterol diet induced hepatic steatosis, insulin resistance and liver dysfunction. Administration of liraglutide effectively alleviated hepatic oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 94%
“…[16][17][18] It has been reported that liraglutide reduces tumor necrosis factor (TNF)-α or high glucose induced oxidative stress and inflammatory response in human endothelial cells. 19,20) Inhibition of protein kinase C (PKC) translocation, reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation and nuclear factor (NF)-κB activation may contribute to the anti-oxidative and anti-inflammatory effects of liraglutide. 19,20) Recently, liraglutide has been reported to reduce the level of plasma reactive oxygen metabolites, an indicator of oxidative stress, in patients with type 2 diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore shows a vasoprotective effect. [25][26][27] It is thought that the vasoprotective effects of the therapeutic agents like, metformin 24 , thiazolidinediones and statins also occur via the AMPK activation. 21 AMPK activation causes the NO-mediated relaxation in the spontaneously hypertensive rats.…”
Section: Adenosine Monophosphate-activated Protein Kinase Pathwaymentioning
confidence: 99%
“…23 Antidiabetic agents, such as, metformin 24 , thiazolidinediones, glukagon like peptid-1 agonists, dipeptidyl peptidase-4 inhibitors, statins, adiponectin and the leptin hormone increase the AMPK activation. 25,26 Experimentally, 5-aminoimidazole-4-carboxamide ribonucleoside is used for the AMPK activation 24 , whereas the dorsomorphine (compound C) is used for the inhibition.…”
Section: Adenosine Monophosphate-activated Protein Kinase Pathwaymentioning
confidence: 99%